Analysis of Organizational Performance in Confection SMEs in Sleman, Indonesia - Tri Wahyuningsih; Yuli Liestyana; Rinaldi Choirul Muarif (Journal of International Conference Proceedings, 2021)
The purpose of this research was to determine the direct effect of entrepreneurial orientation, also the indirect effect of entrepreneurial orientation on the organizational performance of SMEs in the district Sleman through the mediating effect of TQM. This research was made using quantitative research methods using 53 confectionery businesses in Sleman Regency as the research population. The sampling technique in this study used census sampling. Data collection techniques were carried out using a questionnaire as a research instrument. From the results of research and data testing, it can be seen that the entrepreneurial orientation affects the total quality management (TQM) of the confectionery business in Sleman Regency, the entrepreneurial orientation affects the organizational performance of the confectionery business in Sleman Regency, TQM   affects the performance organizational   SMEs confection in Sleman, and there is the indirect effect of orientation entrepreneurial organizational performance through TQM